The common school awakening religion and the transatlantic roots of American public education - Komline, David (New York, NY Oxford University Press, 2020)
Joseph Lancaster, monitorial education, and Christianity without sectarianism -- "The schoolmaster is abroad" : early international influences on American education -- Early attempts at revival in Massachusetts -- The "Prussian system" : origins and transmission -- "The educational regeneration of New England" : the height of the awakening in Massachusetts -- The common school awakening in Ohio -- An awakening for whom? : tensions in Ohio -- Epilogue : the end of the awakening.
"A statue of Horace Mann, erected in front of the Boston State House in 1863, declares him the "Father of the American Public School System." For over a century and a half, most narratives about early American education have proceeded as if this epithet were true. It has been etched into the general American consciousness as surely as it has been etched into the stone pedestal on which Mann stands. As Mann looms over the Boston Common, so he has loomed over discussions of early American schooling. The Common School Awakening offers a new narrative about the rise of public schools in America. The story begins before Horace Mann ever entered the scene as the first Secretary of the Massachusetts Board of Education. In the first half of the nineteenth century a broad and distinctly American religious consensus emerged, allowing people from across the religious spectrum to cooperate in systematizing and professionalizing America's schools, all in an effort to Christianize the country. At the height of this movement, several states introduced state-sponsored teacher training colleges and concentrated government oversight of schools in offices such as the one held by Mann. Shortly thereafter, the religious consensus that had served as the foundation for this common school system disintegrated. But the system itself remained, the legacy not just of one man, but of a whole network of reformers who put into motion a transatlantic and transdenominational religious movement - the "Common School Awakening.""--
Includes bibliographical references and index
Keywords: Public Schools -- United States -- History -- 19th century; Church and education -- United States -- History -- 19th century; Education -- Aims and objectives -- United States -- History -- 19th century